Det vita rummet: Om konstutställningsrummets utveckling, funktion och mening - Simonsson, Märit (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
The white room is an exhibition space that has come to be stereotypical in museums and art galleries in the Western world during the 20th century, with white or one-colored walls, paintings hanging in a row at eye-level and with space in-between. Established as an exhibition space in the early 20th century, as a result of the growing interest in the arts, its impact on the viewer and the autonomy of the artists, the room’s main function is to emphasize the artworks and enhance the art experience for the viewer by reducing distracting elements, dramatic colors and the number of paintings. The plain design of the room also opens up for the visitors own imagination and has an effect on his/her encounter with the exhibition: the visitor’s previous experiences fill the space with meaning beyond mere function.